Strengthening of the cross-section of steel i-beams in the tension zone: a review of scientific research - Reka, Andriy; Galinska, Tatiana; Ovsii, Dmytro; Hajiyev , Mukhlis (Academic journal Industrial Machine Building Civil Engineering, 2024)
The article reviews scientific research on methods and means of strengthening steel beam structural elements by increasing (building up) cross-sections using additional elements made of steel rolled profiles, plates, reinforcing bars and plates made of polymeric materials. The main conclusions and directions of further scientific research on effective methods and means of strengthening steel beam structural elements by increasing (building up) their cross-sections, which have the potential for widespread use in the repair and reconstruction of buildings and structures, are substantiated.